Control of backward-facing step flow using DBD plasma actuator (Effect of frequency and duty ratio of burst modulation) - Satoshi KIKUCHI; Yasuaki KOZATO; Keunseob LEE; Shigeki IMAO (Nihon Kikai Gakkai ronbunshu, 2018)
This study investigates the flow control of backward-facing step flow by a dielectric barrier discharge (DBD) plasma actuator. The DBD plasma actuator is mounted onto the edge of the backward-facing step, and is driven by burst modulation. Velocity measurements, flow visualization, and pressure measurements were carried out.The results demonstrated that the reattachment point is dependent on the burst modulation frequency. When the reattachment point is moved upstream, the vortex frequency in the downstream shear layer becomes to equal the burst modulation frequency. When the reattachment point is moved downstream, the fluctuation of the shear layer weakens, and the shear layer narrows to a width that is less than that of downstream non-control. When the duty ratio of the burst modulation drive is outside of a certain range, the effect of control is reduced. In the case that the reattachment point moves upstream, the upper limit of the duty ratio at which the control effect does not change is determined by the off-time length of burst modulation, whereas the lower limit of the duty ratio is determined by the on-time length of burst modulation. In the case that the reattachment point moves downstream, the upper limit of the duty ratio at which the control effect does not change is independent of the modulation frequency.